Pendapat Ulama tentang Implementasi Akad Qard dan Akad Rahn dalam Perekonomian Islam - Hardiati, Neni; F, Fitriani; Nugroho, Wahyu (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Qardh and Rahn is one of the contracts that does not require an excess when repaying the loan. In much literature, Qardh and Rah tend to be used with the social principle of helping each other. There are several differences of opinion among scholars regarding Qardh and Rahn, including the Hanafiyah opinion that what can be made Qardh is if an item has the same value, while the Malikiyah, Shaafi'iyyah and Hanabilah allow Qardh for assets that are permitted in the salam contract, whether in weight or measure. , such as gold, silver and food, or from items that have value such as animals. Apart from that, in Rahn, according to Hanafiyah Rukun Rahn is the Ijab Qabul from Rahin and Marhun like other contracts. According to other scholars besides Hanafiyah, there are 4 pillars of Rahn, namely Shigah (Ijab and Qabul), People who have a contract (Raahin and Murtahin), Marhun and Marhun Bihi.